2022
DOI: 10.1021/acs.jmedchem.1c01859
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating Selenium into Heterocycles and Natural Products─From Chemical Properties to Pharmacological Activities

Abstract: Selenium (Se)-containing compounds have emerged as potential therapeutic agents for the treatment of a range of diseases. Through tremendous effort, considerable knowledge has been acquired to understand the complex chemical properties and biological activities of selenium, especially after its incorporation into bioactive molecules. From this perspective, we compiled extensive literature evidence to summarize and critically discuss the relationship between the pharmacological activities and chemical propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
91
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 154 publications
(91 citation statements)
references
References 158 publications
0
91
0
Order By: Relevance
“…However, only rare methods have been reported for the construction of Org‐Se compound libraries up to now. Therefore, the development of selenylation chemistries that suitable for parallel synthesis of Org‐Se library and/or Se‐containing DNA‐encoded library ( Se DEL) are highly needed for the development of seleno‐medicinal chemistry [9,10] …”
Section: Hit Generation: From Traditional High‐throughput Screening T...mentioning
confidence: 99%
See 3 more Smart Citations
“…However, only rare methods have been reported for the construction of Org‐Se compound libraries up to now. Therefore, the development of selenylation chemistries that suitable for parallel synthesis of Org‐Se library and/or Se‐containing DNA‐encoded library ( Se DEL) are highly needed for the development of seleno‐medicinal chemistry [9,10] …”
Section: Hit Generation: From Traditional High‐throughput Screening T...mentioning
confidence: 99%
“…Notably, accumulated evidence in chemical biology and medicinal chemistry has indicated that the special chemical properties of Se play a key role in the pharmacological activity, toxicity and metabolic property of Org-Se compounds. [3,9,10] The incorporation of Se into small molecules or natural products have been reported to bring additional benefits, which are closely correlated with the specific Se species as well as their ability to modulate the oxidative stress status of cells, mainly including antioxidation and prooxidation (Figure 1). [9,10] All of these merits indicate the versatile ability of Se in medicinal chemistry.…”
Section: Background: Selenium Is An Emerging Player In Medicinal Chem...mentioning
confidence: 99%
See 2 more Smart Citations
“…As a crucial component of selenoprotein, selenium (Se) is implicated in numerous cellular physiological processes and is crucial for human health and disease. In recent years, growing interest has been paid to Se-containing compounds due to their therapeutic potential against cancer and other diseases by modulating cellular redox status. Se-containing compounds as anticancer agents (such as Ebselen, 2 ) possess pro-oxidative capabilities at higher concentrations, and there is evidence for their high efficiency and selectivity to cancer cells. The arylselenium compounds, such as phenylselenide, represent a group of simple anticancer molecules. Significant evidence was provided that the introduction of phenylselenyl (PhSe) into small molecules was beneficial for modulating their redox ability, enhancing their uptake, improving their efficacy, and antagonizing drug resistance. The hybrid compounds ( 3 ) consisting of PhSe and quinone redox centers exhibited a significant and selective antineoplastic activity through increasing ROS levels to alter the redox levels of cancer cell. Hydantoin derivative ( 4) with a PhSe tail displayed more potent inhibitory activities in resistant T-lymphoma cells probably due to PhSe moiety .…”
Section: Introductionmentioning
confidence: 99%